"I'm not a freshi": Culture shock, puberty and growing up as British-Bangladeshi girls. (August 2020) - Houghton, Lauren C.; Troisi, Rebecca; Sommer, Marni; Katki, Hormuzd A.; Booth, Mark; Choudhury, Osul A.; Hampshire, Kate R.
Abstract: Early puberty is a risk factor for adult diseases and biomedical and psychosocial research implicate growth (in height and weight) and stress as modifiable drivers of early puberty. Seldom have studies examined these drivers simultaneously or concurrently using quantitative and qualitative methods. Within the context of migration, we used mixed-methods to compare growth, stress and puberty in a study of 488 girls, aged 5–16, who were either Bangladeshi, first-generation migrant to the UK, second-generation migrant, or white British (conducted between 2009 and 2011). Using a biocultural framework, we asked the questions: 1) Does migration accelerate pubertal processes? 2) What biocultural markers are associated with migration? 3) What biocultural markers are associated with puberty? Girls self-reported pubertal stage, recalled 24-h dietary intake, and answered questions relating to dress, food, and ethnic identity. We collected anthropometrics and assayed saliva specimens for dehydroepiandrosterone-sulfate (DHEA-S) to assess adrenarcheal status. Our findings demonstrate that first-generation migrants had earlier puberty than second-generation migrants and Bangladeshi girls. British style of dress did not increase with migration, while dietary choices did, which were reflected in increasing body mass index. However, the widely-used phrase, "I'm proud of my religion, but not my culture" demonstrated that ethnic identity was aligned more with Islamic religion than 'Bangladeshi culture.' This was epitomized by wearing the hijab, but denial of eating rice. The social correlates of puberty, such as 'practicing' wearing the hijab and becoming 'dedicated to the scarf, ' occurred at the same ages as adrenarche and menarche, respectively, among first-generation girls. We suggest that the rejection of 'Bangladeshi culture' might be a source of psychosocial stress for first-generation girls, and this may explain elevated DHEA-S levels and early puberty compared to their second-generation counterparts. Our results support a biocultural model of adolescence, a period for biological embedding of culture, when biological and psychosocial factors adjust developmental timing with potential positive and negative implications for long-term health. Highlights: Compares puberty in migrant Bangladeshi girls in the UK using mixed-methods. Argues that stigma may explain early maturation in first-generation migrants. Reveals overlapping ages of biological and cultural puberty in migrant girls. Generates new biocultural hypotheses via hormonal, growth and social stigma data.